The Implementation of Regional Regulations in the Process of Filling in the Village Civil Service - Siti Zuliyah; Triwahyuningsih Triwahyuningsih (Jurnal Daulat Hukum, 2021)
The purpose of this study, firstly, is to describe the process of filling in the Village Civil Service Officer in Sleman Regency, Yogyakarta Special Region and secondly to find out whether the mechanism for filling out the Village Civil Service Officer is in accordance with Regional Regulation No. 10 of 2019. This research is an empirical legal research, namely legal research that examines and analyzes people's behavior in relation to the law. The approach method uses a juridical, sociological approach. Methods of data collection through literature study, interviews and observations, then the data were analyzed by qualitative descriptive method. The results of the study concluded that the process of filling in the village civil service in Sleman Regency: The village head formed an appointment committee to conduct screening and screening through the selection of administrative requirements and administering the exam. Furthermore, the results of the selection of candidates for village civil service at least 2 (two) candidates based on the highest score are requested for consultation with the sub-district head to obtain a recommendation to be appointed as village administrator. 10 of 2019 can be applied according to the rules, namely the formation of a committee, administrative selection, exam materials, a team of examiners, but there are still weaknesses, including the requirements for candidates who are considered burdensome, must be supported by at least 15% of the population, lack of socialization, the existence of several villages that are less open in the process of filling the village civil service.